Hard carbon material and preparation method thereof, negative electrode sheet, sodium ion battery and electrical equipment

By building a gradient-distributed pore structure in hard carbon materials, the problem of poor kinetic performance of existing hard carbon materials in sodium-ion batteries is solved, and the effects of high capacity, high rate performance and low sodium precipitation risks are achieved.

CN118867236BActive Publication Date: 2025-01-21SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411320912.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing hard carbon materials have poor kinetic performance in sodium ion whole batteries, making it difficult to take into account both high capacity and high rate performance, and there are major potential for sodium analysis.

Method used

A non-porous hard carbon core is used to coat at least two layers of pore-forming hard carbon layers, and the outer layer is coated with a non-porous carbon coating layer. The porosity and thickness of the pore-forming hard carbon layer are controlled to increase along the radial gradient of the particles, and the pore diameter range is 0.5nm-1.0nm.

Benefits of technology

A hard carbon anode material for sodium-ion batteries with high capacity, high first efficiency, high compaction, and high kinetic performance has been realized, reducing the hidden danger of sodium evolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118867236B_ABST
    Figure CN118867236B_ABST
Patent Text Reader

Abstract

The present application provides a hard carbon material and its preparation method, anode sheet, sodium ion battery and electrical equipment, and relates to the field of new energy technology. The hard carbon material includes a non-porous hard carbon kernel, at least two layers of pore-forming hard carbon layers coated with the non-porous hard carbon kernel, and a non-porous carbon coating layer coated with the pore-forming hard carbon layer, and the pore-forming hard carbon layer with the highest porosity is placed in the outer layer, and its thickness is controlled at the same time, so that its high sodium storage capacity can be exerted, and its influence on the kinetic performance of sodium ion transmission can be minimized; At the same time, in the radial direction, as the hard carbon material particles go deeper, the porosity of the pore-forming hard carbon layer gradually decreases, so as to maintain the rapid transmission of sodium ions inside the particles, while ensuring high compaction performance; The pore size range of the pores in the pore-forming hard carbon layer is 0.5nm-1.0nm, which is conducive to the storage of sodium ions, can increase capacity, and improve compaction performance; Finally, a thin layer of non-porous carbon is coated in its outermost layer, so as to reduce the specific surface and improve the purpose of the first effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a hard carbon material and a preparation method thereof, a negative electrode sheet, a sodium ion battery and electrical equipment. Background Art

[0002] Sodium-ion batteries have the advantages of abundant sodium resources, low cost, high safety, good rate performance, fast charging advantages, and environmental friendliness, which makes sodium-ion batteries have broad application prospects in new energy vehicles, large-scale electrochemical energy storage systems and other fields. For sodium-ion batteries, there are not many options for negative electrode materials with commercial prospects, and hard carbon is one of them. At present, there are still some challenges in the application of hard carbon materials in sodium-ion full batteries. The most important of these is that their kinetic performance is poor, it is difficult to take into account both high capacity and high rate performance, and there is a large risk of sodium precipitation. Summary of the invention

[0003] The purpose of this application is to provide a hard carbon material and a preparation method thereof, a negative electrode sheet, a sodium ion battery and an electrical device, aiming to solve the problem that existing hard carbon materials are difficult to achieve both high capacity and high rate performance and have a large risk of sodium precipitation.

[0004] To achieve the above objectives, the present application provides a hard carbon material, comprising: a non-porous hard carbon core, at least two pore-forming hard carbon layers covering the non-porous hard carbon core, and a non-porous carbon coating layer covering the pore-forming hard carbon layer;

[0005] The porosity of each layer of the pore-forming hard carbon layer gradually increases in the direction from the inside to the outside of the hard carbon material; the thickness of each layer of the pore-forming hard carbon layer gradually decreases in the direction from the inside to the outside of the hard carbon material;

[0006] The pores in the pore-forming hard carbon layer have a pore diameter ranging from 0.5 nm to 1.0 nm.

[0007] In some embodiments, at least one of the following conditions is met:

[0008] A. The porosity of each layer of the pore-forming hard carbon layer is independently 1%-30%;

[0009] B. The thickness of each layer of the pore-forming hard carbon layer is independently 0.1-3 μm;

[0010] C. The number of layers of the pore-forming hard carbon layer is 2-10;

[0011] D. The particle size D50 of the selected non-porous hard carbon core is 1-3 μm;

[0012] E. The particle size D50 of the hard carbon material is 5-10 μm;

[0013] F. The specific surface area of ​​the hard carbon material is 2-5m 2 / g;

[0014] G. The tap density of the hard carbon material is 0.7-1.0 g / cc;

[0015] H. The 3T powder compaction density of the hard carbon material is 0.93-1.10 g / cc.

[0016] In some embodiments, at least one of the following conditions is met:

[0017] A. The porosity of each layer of the pore-forming hard carbon layer is independently 5%-20%;

[0018] B. The thickness of each layer of the pore-forming hard carbon layer is independently 0.5-2 μm;

[0019] C. The number of layers of the pore-forming hard carbon layer is 2-4.

[0020] The present application also provides a method for preparing the above-mentioned hard carbon material, comprising:

[0021] The mixed solution of the hydrothermal carbon source and the template agent is subjected to at least two hydrothermal reactions, wherein the first hydrothermal reaction is carried out with the nonporous hard carbon dispersed in the mixed solution, and the subsequent hydrothermal reactions are carried out with the product of the previous hydrothermal reaction dispersed in the mixed solution to obtain a composite material;

[0022] Pre-carbonizing and acid-washing the composite material to obtain a purified material;

[0023] The purified material is mixed with a coating agent and sintered to obtain the hard carbon material.

[0024] In some embodiments, the preparation method satisfies at least one of the following conditions:

[0025] A. The hydrothermal carbon source includes at least one of glucose, sucrose and fructose;

[0026] B. the template comprises at least one of magnesium gluconate and calcium gluconate;

[0027] C. The mass ratio of the hydrothermal carbon source to the template is 1 to 1000;

[0028] D. The temperature of the hydrothermal reaction is 150-200°C and the time is 1-6 hours.

[0029] In some embodiments, the nonporous hard carbon includes one or more combinations of biomass hard carbon, sugar hard carbon, resin hard carbon, polymer hard carbon, and fossil hard carbon;

[0030] The non-porous hard carbon satisfies at least one of the following conditions:

[0031] A. The particle size D50 of the selected non-porous hard carbon is 1-3 μm;

[0032] B. The biomass hard carbon is selected from one or a combination of at least two of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, chestnut shell, hazelnut shell, peanut shell, walnut shell, peach shell, cotton, wood, bamboo, straw, and lignin;

[0033] C. The sugar hard carbon includes one or a combination of at least two of glucose, sucrose, maltose, lactose, fructose, starch, and cellulose;

[0034] D. The resin hard carbon comprises one or a combination of at least two of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine resin, polyimide resin, polyester resin, polyaldehyde resin, polyolefin resin, and polyacrylic resin;

[0035] E. The polymer hard carbon includes one or a combination of at least two of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber or polyacrylonitrile.

[0036] In some embodiments, the preparation method satisfies at least one of the following conditions:

[0037] A. The pre-carbonization temperature is 400°C-800°C, and the holding time is 0.5-24h;

[0038] B. The pre-carbonization atmosphere is an inert gas atmosphere or an oxygen-deficient atmosphere; the inert gas is one or a combination of at least two of nitrogen, argon, neon, helium, xenon or krypton; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of ≤1wt%;

[0039] C. The stirring time of the pickling is 0.5-24h, and the washing is performed until the pH value is 4-8;

[0040] D. The acid used for pickling is one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid;

[0041] E. The added mass of the coating agent is 1% to 10% of the mass of the purified material;

[0042] F. The coating agent is one or a combination of asphalt and resin;

[0043] G. The sintering temperature is 800°C-1600°C, the heating rate is 0.5-10°C / min, and the holding time is 0.5-24h;

[0044] H. The sintering gas atmosphere is an inert gas atmosphere; the inert gas is one of nitrogen, argon, neon, helium, xenon or krypton, or a combination of at least two of them.

[0045] The present application also provides a negative electrode sheet, comprising the above-mentioned hard carbon material.

[0046] The present application also provides a sodium ion battery, comprising the above-mentioned negative electrode sheet.

[0047] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0048] Compared with the prior art, the beneficial effects of this application include:

[0049] The hard carbon material provided by the present application includes a non-porous hard carbon inner core, at least two pore-forming hard carbon layers coating the non-porous hard carbon inner core, and a non-porous carbon coating layer coating the pore-forming hard carbon layer. The pore-forming hard carbon layer with the highest porosity is placed in the outer layer, and its thickness is controlled at the same time, so that its high sodium storage capacity can be exerted and its influence on the kinetic performance of sodium ion transport can be minimized; at the same time, in the radial direction, as the depth goes deeper into the interior of the hard carbon material particles, the porosity of the pore-forming hard carbon layer gradually decreases, so as to maintain the rapid transport of sodium ions inside the particles while ensuring high compaction performance; the pores in the pore-forming hard carbon layer have a pore size range of 0.5nm-1.0nm, which is conducive to the storage of sodium ions, can increase capacity, and improve compaction performance; finally, a thin layer of non-porous carbon is coated on its outermost layer to achieve the purpose of reducing the specific surface and improving the initial effect. The present application provides a hard carbon negative electrode material for sodium ion batteries that has high capacity, high initial efficiency, high compaction and high kinetic performance by finely regulating the pore structure of the hard carbon material and controlling the porosity to increase gradually along the radial direction of the particle from the inside to the outside. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0051] Figure 1 Schematic diagram of the structure of the hard carbon material and the sodium ion migration diagram of Example 1;

[0052] Figure 2 The particle size distribution diagram of the non-porous hard carbon core of Example 1, the product after the first pore-forming coating, the product after the second pore-forming coating, the product after the third pore-forming coating, and the final asphalt-coated product;

[0053] Figure 3 is a SEM image of the nonporous hard carbon core of Example 1;

[0054] Figure 4 This is a SEM image of the porous intermediate product after three pore-forming coatings in Example 1;

[0055] Figure 5 is a SEM image of the hard carbon material of Example 1;

[0056] Figure 6 The pore size distribution diagram of the non-porous hard carbon core of Example 1 and the product after three-time pore formation and coating;

[0057] Figure 7 The first-week charge-discharge curves of Example 1, Comparative Example 2 and Comparative Example 4 are shown, wherein the right part is a partial enlarged view of the left part;

[0058] Figure 8 Schematic diagram of the structure of the hard carbon material of Comparative Example 1 and schematic diagram of sodium ion migration. DETAILED DESCRIPTION

[0059] As used herein:

[0060] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0061] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0062] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0063] In these examples, parts and percentages are by mass unless otherwise indicated.

[0064] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.

[0065] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0066] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0067] Example 1

[0068] Embodiment 1 First, a hard carbon material is provided. Spherical resin hard carbon with D50=2 μm is selected as a non-porous hard carbon core. The preparation method of the hard carbon material comprises the following steps:

[0069] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is carried out to form pores and coat it to obtain a porous carbon. The product is centrifuged and dried.

[0070] (2) The hydrothermal step is then repeated. 40 g of the product of step (1) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and after dissolution and dispersion, hydrothermal treatment is performed to perform secondary pore formation and coating to obtain mesoporous carbon. The product is centrifuged and dried.

[0071] (3) Repeat the hydrothermal step again. Dry 50 g of the product in step (2), take 30 g of glucose and 15 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment three times to form pores and coat the porous carbon. Centrifuge and dry the product.

[0072] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0073] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0074] (6) Mix the product of step (5) with asphalt, with the mass ratio of asphalt added being 5%.

[0075] (7) The mixed product of step (6) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of Example 1, whose physical parameters are shown in Table 1.

[0076] Figure 1 A schematic diagram of the structure of the hard carbon material of this embodiment and a schematic diagram of sodium ion migration are shown; Figure 2 The particle size distribution of the non-porous hard carbon core, the product after the first pore-forming coating, the product after the second pore-forming coating, the product after the third pore-forming coating, and the final asphalt-coated product is shown. Figure 2 It can be found that as the pore-forming coating layer increases, the particle size also increases synchronously.

[0077] Figure 3 SEM images showing the nonporous hard carbon core, Figure 4 The SEM image of the porous intermediate product after three pore-forming coatings after acid washing and template removal in step (5) is shown. Figure 5 The SEM image of the final hard carbon product of step (7) is shown.

[0078] Figure 6 The pore size distribution diagram of the non-porous hard carbon core and the product after three-time pore-forming coating is shown. The left part is the mesopore distribution diagram of the N2 test, which shows that the non-porous hard carbon core of Example 1 and the product after three-time pore-forming coating have almost no mesopores, and the right part is the micropore distribution diagram of the CO2 test, which shows that the non-porous hard carbon core of Example 1 has almost no micropores, and the product after three-time pore-forming coating is mainly micropores. The pore size distribution characterization of the intermediate products at different stages shows that the template pore-forming method adopted in Example 1 has a pore size concentrated between 0.5 and 0.8 nm.

[0079] The hard carbon material, conductive agent (SP) and binder (LA133) of Example 1 were mixed in a ratio of 91:3:6 by mass to obtain a mixture, the solid content of the mixture was adjusted to 50% with deionized water, and the mixture was mixed evenly to obtain a slurry. The slurry was coated on a copper foil current collector, vacuum dried and rolled to obtain a surface density of 5.5±0.5 mg / cm 2The negative electrode.

[0080] Button cell production: Sodium sheet as counter electrode, 1 mol / L NaPF6, EC / EMC / DMC (volume ratio of 1:1:1) as electrolyte, glass fiber as separator, 2032 button cell shell, assembled to obtain button half cell. Test system is as follows: discharge: 0.1C discharge to 1 mV, 50 μA discharge to 1 mV, 10 μA discharge to 1 mV; charge: 0.1C charge to 2 V, nominal capacity is 350 mAh / g.

[0081] The battery performance of the button-type half-cell was tested, and the test results are shown in Table 2. Figure 7 The first-week charge and discharge curves of Example 1 and Comparative Examples 2 and 4 are shown.

[0082] Example 2

[0083] Embodiment 2 First, a hard carbon material is provided, coconut shell carbon with D50=2 μm is selected as a non-porous hard carbon core, and the preparation method of the hard carbon material comprises the following steps:

[0084] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0085] (2) The hydrothermal step is then repeated. 40 g of the product from step (1) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0086] (3) The product of step (2) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 500°C, for 5 hours.

[0087] (4) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0088] (5) Mix the product of step (4) with asphalt, with the mass ratio of asphalt added being 3%.

[0089] (6) The mixed product of step (5) was sintered at 1300°C for 5 h in a nitrogen atmosphere at a heating rate of 3°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of Example 2, whose physical parameters are shown in Table 1.

[0090] The hard carbon material of Example 2 was assembled into a sodium ion button half-cell using the same method as Example 1 for testing. The battery performance is shown in Table 2.

[0091] Example 3

[0092] Embodiment 3 First, a hard carbon material is provided. Starch-based hard carbon with D50=2 μm is selected as the non-porous hard carbon core hard carbon. The preparation method of the hard carbon material comprises the following steps:

[0093] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0094] (2) The hydrothermal step is then repeated. 40 g of the product from step (1) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0095] (3) Repeat the hydrothermal step again. Take 50 g of the product from step (2) and dry it. Take 30 g of glucose and 15 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment for three times of pore formation and coating. The product is then centrifuged and dried.

[0096] (4) Repeat the hydrothermal step again. Dry 50 g of the product in step (3), take 15 g of glucose and 15 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment, perform pore formation and coating four times, and centrifuge and dry the product.

[0097] (5) The product of step (4) was pre-carbonized at 550°C for 2 hours at a heating rate of 5°C per minute under a nitrogen atmosphere.

[0098] (6) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0099] (7) Mix the product of step (6) with asphalt, with the mass ratio of asphalt added being 5%.

[0100] (8) The mixed product of step (7) was sintered at 1500°C for 2 h in a nitrogen atmosphere at a heating rate of 2°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of Example 3, whose physical parameters are shown in Table 1.

[0101] The hard carbon material of Example 3 was assembled into a sodium ion button half-cell using the same method as Example 1 for testing. The battery performance is shown in Table 2.

[0102] Example 4

[0103] Embodiment 4 First, a hard carbon material is provided. Polyethylene glycol hard carbon with D50=2 μm is selected as the non-porous hard carbon core. The preparation method of the hard carbon material comprises the following steps:

[0104] (1) Take 88 g of glucose and 2 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0105] (2) The hydrothermal step is then repeated. 40 g of the product from step (1) is dried, 75 g of glucose and 10 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0106] (3) Repeat the hydrothermal step again. Take 50 g of the product from step (2) and dry it. Take 30 g of glucose and 10 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment for three times of pore formation and coating. The product is then centrifuged and dried.

[0107] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0108] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0109] (6) Mix the product of step (5) with asphalt, with the mass ratio of asphalt added being 3%.

[0110] (7) The mixed product of step (6) was sintered at 1200°C for 5 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of Example 4, whose physical parameters are shown in Table 1.

[0111] The hard carbon material in Example 1 was replaced by the hard carbon material in this embodiment, and a sodium ion button half-cell was assembled using the same method as in Example 1. The battery performance is shown in Table 2.

[0112] Example 5

[0113] Embodiment 5 First, a hard carbon material is provided. Spherical resin hard carbon with D50=2 μm is selected as the non-porous hard carbon core. The preparation method of the hard carbon material comprises the following steps:

[0114] (1) Take 66 g of glucose and 6 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0115] (2) The hydrothermal step is then repeated. 40 g of the product of step (1) is dried, 50 g of glucose and 10 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0116] (3) Repeat the hydrothermal step again. Take 50 g of the product from step (2) and dry it. Take 20 g of glucose and 10 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment for three times of pore formation and coating. The product is then centrifuged and dried.

[0117] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0118] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0119] (6) Mix the product of step (5) with asphalt, with the mass ratio of asphalt added being 5%.

[0120] (7) The mixed product of step (6) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of Example 5, whose physical parameters are shown in Table 1.

[0121] The hard carbon material of Example 5 was assembled into a sodium ion button half-cell using the same method as Example 1 for testing. The battery performance is shown in Table 2.

[0122] Comparative Example 1

[0123] Comparative Example 1 provides a hard carbon material, and the preparation method comprises the following steps:

[0124] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, place them in a 180°C forced air oven and react for 3 hours. Then take them out and naturally cool them to room temperature. The product is centrifuged and dried.

[0125] (2) The product of step (1) was pre-carbonized in a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0126] (3) The carbonized product is acid-washed to remove the magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0127] (4) Mix the product of step (3) with asphalt, with the mass ratio of asphalt added being 5%.

[0128] (5) The mixed product of step (4) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of comparative example 1. The structural schematic diagram and sodium ion migration schematic diagram are shown in FIG. Figure 8 Its physical parameters are shown in Table 1.

[0129] The hard carbon material of Comparative Example 1 was assembled in the same manner as in Example 1 to obtain a sodium ion button half-cell. The battery performance is shown in Table 2.

[0130] Comparative Example 2

[0131] Comparative Example 2 provides a hard carbon material, using spherical resin hard carbon with D50=2μm as the non-porous hard carbon core, and the preparation method includes the following steps:

[0132] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 0.5 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. Perform a pore-forming coating and centrifuge the product to dry.

[0133] (2) The product of step (1) was pre-carbonized in a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0134] (3) The carbonized product is acid-washed to remove the magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0135] (4) Mix the product of step (3) with asphalt, with the mass ratio of asphalt added being 5%.

[0136] (5) The mixed product of step (4) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of comparative example 2, whose physical parameters are shown in Table 1.

[0137] The hard carbon material of Comparative Example 2 was assembled into a sodium ion button half-cell in the same manner as in Example 1 for testing. The battery performance is shown in Table 2.

[0138] Comparative Example 3

[0139] Comparative Example 3 provides a hard carbon material, and the preparation method comprises the following steps:

[0140] (1) Take 30 g of glucose and 3 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, place them in a 180°C forced air oven and react for 3 hours. Then take them out and naturally cool them to room temperature. The product is then centrifuged and dried.

[0141] (2) The product of step (1) was pre-carbonized in a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0142] (3) The carbonized product is acid-washed to remove the magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0143] (4) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of the product of step (3) as the core hard carbon and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. Perform a pore-forming coating and centrifuge the product to dry.

[0144] (5) The hydrothermal step is then repeated. 40 g of the product from step (4) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0145] (6) Repeat the hydrothermal step again. Dry 50 g of the product in step (5), take 30 g of glucose and 15 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment, perform pore formation and coating three times, and centrifuge and dry the product.

[0146] (7) The product of step (6) was pre-carbonized in a nitrogen atmosphere at 600°C at a heating rate of 5°C per minute for 3 hours.

[0147] (8) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0148] (9) Mix the product of step (8) with asphalt, with the mass ratio of asphalt added being 5%.

[0149] (10) The mixed product of step (9) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of comparative example 3, whose physical parameters are shown in Table 1.

[0150] The hard carbon material of Comparative Example 3 was assembled into a sodium ion button half-cell in the same manner as in Example 1 for testing. The battery performance is shown in Table 2. When the inner core is less porous, the capacity is slightly higher, but the compaction is low and the kinetic performance is significantly reduced, that is, the rate performance is much worse.

[0151] Comparative Example 4

[0152] Comparative Example 4 provides a hard carbon material, using spherical resin hard carbon with D50=2μm as the non-porous hard carbon core, and the preparation method includes the following steps:

[0153] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 10 g of the non-porous core and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0154] (2) The hydrothermal step is then repeated. 10 g of the product of step (1) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0155] (3) Repeat the hydrothermal step again. Dry 10 g of the product in step (2), take 60 g of glucose and 30 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment, perform pore formation and coating three times, and centrifuge and dry the product.

[0156] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0157] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0158] (6) Mix the product of step (5) with asphalt, with the mass ratio of asphalt added being 5%.

[0159] (7) The mixed product of step (6) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of comparative example 4, whose physical parameters are shown in Table 1.

[0160] The hard carbon material of Comparative Example 4 was assembled into a sodium ion button half-cell in the same manner as in Example 1 for testing. The battery performance is shown in Table 2.

[0161] Comparative Example 5

[0162] Comparative Example 5 provides a hard carbon material, using spherical resin hard carbon with D50=2μm as the non-porous hard carbon core, and the preparation method includes the following steps:

[0163] (1) Take 88 g of glucose and 8 g of zinc gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of core hard carbon and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0164] (2) The hydrothermal step is then repeated. 40 g of the product from step (1) is dried, 75 g of glucose and 15 g of zinc gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0165] (3) Repeat the hydrothermal step again. Take 50 g of the product from step (2) and dry it. Take 30 g of glucose and 15 g of zinc gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment for three times of pore formation and coating. The product is then centrifuged and dried.

[0166] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0167] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0168] (6) Mix the product of step (5) with asphalt, with the mass ratio of asphalt added being 5%.

[0169] (7) The mixed product of step (6) is sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final asphalt-coated product, i.e., the hard carbon material of comparative example 5. Various physical parameters thereof are shown in Table 1. The template used in comparative example 5 is zinc gluconate, and the pores in the obtained pore-forming hard carbon layer have a larger pore size.

[0170] The hard carbon material of Comparative Example 5 was assembled into a sodium ion button half-cell in the same manner as in Example 1 for testing. The battery performance is shown in Table 2.

[0171] Comparative Example 6

[0172] Comparative Example 6 First, a hard carbon material is provided, and spherical resin hard carbon with D50=2 μm is selected as the non-porous core hard carbon. The preparation method of the hard carbon material includes the following steps:

[0173] (1) Take 88 g of glucose and 8 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After they are completely dissolved, take 1 g of core hard carbon and ultrasonically disperse it in the above solution. After ultrasonication for 0.5 h, put it into a stainless steel reactor and then place it in a 180°C forced air oven. After reacting for 3 hours, take it out and naturally cool it to room temperature. The hydrothermal reaction is performed once for pore formation and coating, and the product is centrifuged and dried.

[0174] (2) The hydrothermal step is then repeated. 40 g of the product from step (1) is dried, 75 g of glucose and 15 g of magnesium gluconate are dissolved in 100 mL of deionized water, and the mixture is hydrothermally treated after dissolution and dispersion to perform secondary pore formation and coating. The product is then centrifuged and dried.

[0175] (3) Repeat the hydrothermal step again. Take 50 g of the product from step (2) and dry it. Take 30 g of glucose and 15 g of magnesium gluconate and dissolve them in 100 mL of deionized water. After dissolution and dispersion, perform hydrothermal treatment for three times of pore formation and coating. The product is then centrifuged and dried.

[0176] (4) The product of step (3) was pre-carbonized under a nitrogen atmosphere at a heating rate of 5°C per minute, at 600°C, for 3 hours.

[0177] (5) The carbonized product is acid-washed to remove magnesium oxide generated during the carbonization process, then washed with deionized water to a pH of 4-8 and dried.

[0178] (6) The product of step (5) was sintered at 1400°C for 3 h in a nitrogen atmosphere at a heating rate of 5°C per minute to obtain a final product, i.e., the hard carbon material of Comparative Example 6, whose physical parameters are shown in Table 1.

[0179] The hard carbon material of Comparative Example 6 was assembled in the same manner as in Example 1 to obtain a sodium ion button half-cell. The battery performance is shown in Table 2.

[0180] The physical parameters of the hard carbon materials of various embodiments and comparative examples are shown in Table 1.

[0181] Table 1 Physical parameters of the hard carbon materials of various embodiments and comparative examples

[0182]

[0183] Data testing method in Table 1:

[0184] Porosity: The total pore volume of the material and the true volume of the sample can be determined by measuring the isothermal adsorption-desorption curve of nitrogen / CO2, and then the porosity can be calculated. The test sample is a sample of the tested coating layer after hydrothermal, carbonization and purification.

[0185] Thickness: obtained through particle size test, (D50 after coating - D50 before coating) / 2 = coating layer thickness.

[0186] Pore ​​size: obtained by nitrogen / CO2 adsorption-desorption test. The test samples are samples of the tested coating layer after hydrothermal, carbonization and purification.

[0187] Specific surface area: nitrogen adsorption-desorption test.

[0188] The electrochemical performances of the batteries of various embodiments and comparative examples are shown in Table 2.

[0189] Table 2 Battery performance of each embodiment and comparative example

[0190]

[0191] exist Figure 7 By comparing the first week charge and discharge curves of the hard carbon with a pore-free core and Comparative Example 2, as well as Comparative Example 1 in Table 2, it can be found that increasing the pore structure can significantly improve the sodium storage capacity of the hard carbon, but has a certain reduction in compaction.

[0192] The capacity proportion of the 0.1C segment of the first discharge can effectively reflect the kinetic performance of the hard carbon material. The higher the proportion, the better the kinetic performance. According to the capacity proportion of the 0.1C segment of the first discharge in Table 2, it can be found that increasing the pore structure has a certain reduction in the kinetic performance, but by comparing Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5, it is found that the gradient distribution pore structure design in Example 1 can effectively avoid the influence of the pores on the kinetics. However, the number of pore-forming layers of this gradient distribution should not be too many. When the number of layers exceeds 3 layers, it will have a significant impact on the structural stability of the material, thereby affecting its cycle performance (Example 3).

[0193] Therefore, Example 1 of the present application, by rationally constructing a radially gradient distributed pore structure in the hard carbon material, effectively improves its specific capacity while maintaining optimal electrode compaction, kinetic performance during sodium storage, and cycle stability.

[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0195] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A hard carbon material, characterized in that: include: A nonporous hard carbon core, at least two pore-forming hard carbon layers covering the nonporous hard carbon core, and a nonporous carbon coating layer covering the pore-forming hard carbon layers; The porosity of each layer of the pore-forming hard carbon layer gradually increases in the direction from the inside to the outside of the hard carbon material; the thickness of each layer of the pore-forming hard carbon layer gradually decreases in the direction from the inside to the outside of the hard carbon material; The pores in the pore-forming hard carbon layer have a pore size range of 0.5 nm to 1.0 nm; The porosity of each layer of the pore-forming hard carbon layer is independently 5%-20%; The thickness of each layer of the pore-forming hard carbon layer is independently 0.5-2 μm; The number of layers of the pore-forming hard carbon layer is 3.

2. The hard carbon material according to claim 1, characterized in that At least one of the following conditions is met: A. The particle size D50 of the selected non-porous hard carbon core is 1-3 μm; B. The particle size D50 of the hard carbon material is 5-10 μm; C. The specific surface area of ​​the hard carbon material is 2-5m 2 / g; D. the tap density of the hard carbon material is 0.7-1.0 g / cc; E. The 3T powder compaction density of the hard carbon material is 0.93-1.10 g / cc.

3. A method for preparing a hard carbon material according to any one of claims 1 to 2, characterized in that: include: The mixed solution of the hydrothermal carbon source and the template agent is subjected to at least two hydrothermal reactions, wherein the first hydrothermal reaction is carried out with the nonporous hard carbon dispersed in the mixed solution, and the subsequent hydrothermal reactions are carried out with the product of the previous hydrothermal reaction dispersed in the mixed solution to obtain a composite material; Pre-carbonizing and acid-washing the composite material to obtain a purified material; The purified material is mixed with a coating agent and sintered to obtain the hard carbon material; The hydrothermal carbon source includes at least one of glucose, sucrose and fructose; The template agent includes at least one of magnesium gluconate and calcium gluconate.

4. The method for preparing a hard carbon material according to claim 3, characterized in that: The preparation method satisfies at least one of the following conditions: A. The mass ratio of the hydrothermal carbon source to the template is 1 to 1000; B. The temperature of the hydrothermal reaction is 150-200°C and the time is 1-6 hours.

5. The method for preparing a hard carbon material according to claim 3, characterized in that: The non-porous hard carbon includes one or more combinations of biomass hard carbon, sugar hard carbon, resin hard carbon, polymer hard carbon, and fossil hard carbon; The non-porous hard carbon satisfies at least one of the following conditions: A. The particle size D50 of the selected non-porous hard carbon is 1-3 μm; B. The biomass hard carbon is selected from one or a combination of at least two of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, chestnut shell, hazelnut shell, peanut shell, walnut shell, peach shell, cotton, wood, bamboo, straw, and lignin; C. The sugar hard carbon includes one or a combination of at least two of glucose, sucrose, maltose, lactose, fructose, starch, and cellulose; D. The resin hard carbon comprises one or a combination of at least two of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine resin, polyimide resin, polyester resin, polyaldehyde resin, polyolefin resin, and polyacrylic resin; E. The polymer hard carbon includes one or a combination of at least two of polyfurfuryl alcohol, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, natural rubber or polyacrylonitrile.

6. The method for preparing a hard carbon material according to claim 3, characterized in that: The preparation method satisfies at least one of the following conditions: A. The pre-carbonization temperature is 400°C-800°C, and the holding time is 0.5-24h; B. The pre-carbonization atmosphere is an inert gas atmosphere or an oxygen-deficient atmosphere; the inert gas is one or a combination of at least two of nitrogen, argon, neon, helium, xenon or krypton; the oxygen-deficient atmosphere is a gas atmosphere with an oxygen content of ≤1wt%; C. The stirring time of the acid washing is 0.5-24h, and the washing is performed until the pH value is 4-8; D. The acid used for pickling is one or a combination of at least two of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid; E. The added mass of the coating agent is 1% to 10% of the mass of the purified material; F. The coating agent is one or a combination of asphalt and resin; G. The sintering temperature is 800°C-1600°C, the heating rate is 0.5-10°C / min, and the holding time is 0.5-24h; H. The sintering gas atmosphere is an inert gas atmosphere; the inert gas is one of nitrogen, argon, neon, helium, xenon or krypton, or a combination of at least two of them.

7. A negative electrode sheet, characterized in that: The hard carbon material comprises the hard carbon material according to any one of claims 1 to 2.

8. A sodium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 7.

9. An electrical device, characterized in that: Including the sodium ion battery as described in claim 8.

Citation Information

Patent Citations

  • Hard carbon negative electrode material with multilayer core-shell structure and preparation method and application thereof

    CN113328067A

  • Negative pole piece, battery, battery pack and electric equipment

    CN117038856A

  • Novel silicon-carbon negative electrode material for lithium ion battery and preparation method of novel silicon-carbon negative electrode material

    CN117936729A